Análise da viabilidade econômica da injeção de vapor a partir da água produzida no poço Araçás Bahia - Moreira Mascarenhas Cordeiro, Filipe; Gomes, Lígia; Pena Forte Silva, Uinna; Andrade, Cássio Henrique; Pimentel Santa Rosa, Licianne; Damasceno da Silva, Laio (Latin American Journal of Energy Research, 2024)
In Brazil, especially in the Northeast region, there is a large number of heavy oil reservoirs where recovery through conventional methods has proven inefficient. In this context, thermal recovery, particularly steam injection, has been widely employed, as heat reduces oil viscosity, significantly facilitating its displacement. This study aims to present an economic analysis of steam injection in oil wells using produced water. To use produced water as steam in heavy oil recovery, treatment is required to remove contaminants, for which an appropriate treatment system has been proposed. The study was conducted in the Araçás field, Bahia, where one hour of steam injection operation was analyzed using water supplied by the local water network to unclog a producing well due to paraffin precipitation along the production column. In light of this, costs and benefits were analyzed for using produced water as a fluid, both for such processes and for heavy oil recovery.